Ancient Greek texts and modern narrative theory towards a critical dialogue - Grethlein, Jonas 1978- (Cambridge University Press, 2023)
"Demonstrates the limits of narratology in understanding ancient texts and forges a new approach that investigates the specific logic of ancient narrative. An invaluable introduction to ancient views of narrative but also a major contribution to a historically sensitive theory of narrative"--
Keywords: Erzähltheorie; Literatur; Griechisch; Narration (Rhetoric) / History; Greek literature / History and criticism; Criticism, interpretation, etc